3D meshless simulation of laser ray deviation under thermal lensing effect. (20th July 2015) - Afsari, Arman; Heidari, Abbasali; Movahhedi, Masoud
Summary: In this study, one of the most important destructive effects in end‐pumped Nd:YAG laser, that is, thermal lensing is analyzed. Different partial differential equations, supplemented by suitable boundary conditions, are solved and joined to illustrate the fluctuations in laser Transverse Electromagnetic (TEM) mode. Because of no analytic demonstration of this effect, an efficient meshless method known as radial point interpolation meshless method (RPIM) is used to simulate the problem divided into two two‐dimensional cases, that is, xz and yz planes so as to be graphically understandable. The results are in good agreement with measurement reports, and the RPIM shows better accuracy than FEM. Copyright © 2015 John Wiley & Sons, Ltd.